Досвідта актуальні питання вимірювань параметрів випромінювання радіоелектронних засобів широкосмугового доступу - Колесніков, О. М. (ХНУРЕ, 2019)
The basic methods of measuring the frequency and bandwidth of radionuclide bandwidths of radio access systems, including wireless LAN equipment in the 2.4 GHz and 5 GHz frequency bands according to the technical requirements of the standards, are presented. Methodology for checking compliance of RES characteristics with modern standards and radiation standards to ensure the electromagnetic compatibility of RES and providing the necessary information for the needs of regulation of the use of the radio frequency resource of Ukraine.
Keywords: IEEE 802.11; РЕЗ; ЕМС; LAN